PENTINGNYA MOTIVASI DALAM PEMBELAJARAN AKUNTANSI SEBAGAI DASAR MANAJEMEN KEUANGAN PRIBADI - Kusumadyahdewi, Kusumadyahdewi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2017)
Accounting in major PIPS less favored by students, but in fact it is very important to apply in daily life, especially in the setting of personal finance. At the beginning to see an accounting class, students are pessimistic to be able to follow properly. Because the average PIPS student does not like calculations. Actually count in accounting are mostly addition and subtraction, while division and multiplication are very rarely used. It is important to clarify to students so that they can change their view to accounting and further motivate.Â Keywords: motivation, social science.